Griess Test Affection (A and B) by Transmission of Contaminants Inside the Barrel of the Shotgun Brand Benelli Super Nova Model (Global Journal of Human-Social Science, 2021)
The present investigation arises from the need to investigate and to experiment scientifically if the contaminants established as controlled variable and not contralada can affect performing the procedure described in clause 4.1 of guide 2DC-GU-0024 on "performing ballistic testing on weapons (firearms, pneumatic, gas, black powder, detonating, electrical, etc.) and entering ballistic identification systems."; It can be reasonably inferred that by performing the forty-two tests, manipulating solutions A and B of the Griess reagent, it is evident that the pollutants transferred to the Interior of the Cannon (4-stroke oil, diesel and gasoline) do not affect the results for the identification of nitrites Product of combustion during the Shooting phenomenon. Case contrary, It happens with rainwater, since it is observed that the same it affects the elaboration of the test, taking into account that without coming into contact with the gunpowder, results in a faint pink coloration, indicating in a preliminary way that it is Positive for presence of nitrites.
Keywords: griess A and B; nitrites; nitrates; deflagration; combustion